The Moderating Role of Job Satisfaction on Workplace Absenteeism and Substance use amongst the Employees at a Power Utility in Mpumalanga - Jaarsveld, Diana van; Keyser, ElsabÃ (Journal of Economics and Behavioral Studies, 2018)
This article concentrates on the extent to which job satisfaction predicts absenteeism and substance use levels, and also investigates the moderating effect of job satisfaction on absenteeism and substance use levels amongst employees at a power utility in Mpumalanga. This study is based on data gathered from a survey regarding job satisfaction, absenteeism and the substance consumption levels of employees, its antecedents and outcomes. A total of 239 permanent employees based at a power utility in Mpumalanga participated in the research study. These employees were employed in a permanent position at the power utility, gave consent to participate in the research study willingly and were employed for more than three months. The core findings of this study revealed that the frequency of substance consumption influences employee absenteeism and that job satisfaction indeed plays a moderating role on the relationship between substance consumption levels and employee absenteeism. The findings of this study can assist management to understand the relationship between substance consumption and absenteeism and how job satisfaction influences this relationship in order torestrict unnecessary absenteeism properly. The study added value to the field of study by providing complementary scientific research to the lacking literature. In addition, it confirms international findings and its applicability in the energy sector.